Organic-inorganic hybrid wear-resistant antifogging coating, preparation method and application thereof, and organic-inorganic hybrid wear-resistant antifogging coating
Through the preparation and application of organic and inorganic hybrid wear-resistant anti-fog coatings, the problems of fogging and dust adsorption on the surface of optical equipment are solved, and the high strength, hydrophilicity and multifunctional performance of the coating are achieved, and the anti-fog, self-cleaning and wear-resistant properties of the equipment are improved.
Patent Information
- Application Number
- CN202510081894.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Due to fogging and dust adsorption on the surface of optical equipment, the visibility, reduced luminous flux and imaging clarity are affected, making it difficult for existing coatings to have anti-fog, self-cleaning and wear resistance.
Using organic and inorganic hybrid wear-resistant anti-fog coating, the coating is formed by hydrolysis of aminosilane, modification of amino-aminosilia and nano-silia spheres, combining silica sol and titanium dioxide to form a high-strength, hydrophilic coating, and the coating film formation is achieved through UV curing technology.
It achieves excellent hydrophilic effect, wear resistance, water resistance and anti-static properties of the coating, enhances the anti-fog and self-cleaning capabilities of the optical equipment, and improves the imaging clarity and service life.
Smart Images

Figure CN119775812A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material modification, and in particular to an organic-inorganic hybrid wear-resistant anti-fog coating, a preparation method and application thereof, and an organic-inorganic hybrid wear-resistant anti-fog coating. Background Art
[0002] The fogging of the optical device surface not only reduces visibility, but also condenses water droplets on the substrate surface, causing light scattering and reducing light flux, affecting the clarity of optical device imaging. In addition to fogging caused by temperature and humidity changes, dust and pollutants in the air are easily adsorbed on the device surface under the action of static electricity, hindering the normal operation of the device. It is a great responsibility to develop functional coatings that have both anti-fog and self-cleaning functions to meet display needs. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide an organic-inorganic hybrid wear-resistant anti-fog coating and its preparation method and application, and an organic-inorganic hybrid wear-resistant anti-fog coating. The organic-inorganic hybrid wear-resistant anti-fog coating prepared by the preparation method of the present invention can make the wear-resistant anti-fog coating finally prepared have excellent hydrophilic effect, and also have excellent comprehensive properties such as wear resistance, water resistance and antistatic.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing an organic-inorganic hybrid wear-resistant anti-fog coating, comprising the following steps:
[0006] After hydrolyzing the aminosilane, the hydrolyzed aminosilane is mixed with a silica dispersion and subjected to a first heating to obtain amino silica;
[0007] The amino-silica, propane sultone and the first solvent are mixed and heated for a second time to obtain zwitterion-modified nano-silica spheres;
[0008] The zwitterion-modified nano silica spheres, silica sol, titanium dioxide, a crosslinking agent, a photoinitiator and a second solvent are mixed to obtain the organic-inorganic hybrid wear-resistant anti-fog coating.
[0009] Preferably, the hydrolysis process comprises: mixing the aminosilane, water and ethanol, and then hydrolyzing under acidic conditions;
[0010] The aminosilane includes one or more of N-aminoethyl-γ-aminopropyltrimethoxysilane, N,N-dimethyl-3-aminopropyltrimethoxysilane, N,N-diethyl-3-(trimethoxysilyl)propylamine, anilinomethyltriethoxysilane, γ-aminopropyltriethoxysilane and polyaminoalkyltrialkoxysilane;
[0011] The mass ratio of aminosilane, water and ethanol is (10-40): (2-15): (50-100);
[0012] The pH value of the acidic condition is 2 to 6; the acid solution providing the acidic condition is one or more of acetic acid, nitric acid and hydrochloric acid, and the mass percentage concentration of the acid solution is 30% to 40%;
[0013] The hydrolysis temperature is 15-25° C. and the time is 1-5 hours.
[0014] Preferably, the silicon dioxide dispersion comprises silicon dioxide nanoparticles and an ethanol aqueous solution;
[0015] The mass ratio of the silicon dioxide nanoparticles to the ethanol aqueous solution is 1:(10-40);
[0016] The volume ratio of ethanol to water in the ethanol aqueous solution is preferably (1-5):1;
[0017] The mass ratio of the hydrolyzed aminosilane to the silicon dioxide nanoparticles is (1-4):1;
[0018] The first heating temperature is 60° C. and the time is 4 to 8 hours.
[0019] Preferably, the mass ratio of the amino silica to propane sultone is (1-3):1;
[0020] The mass ratio of the total mass of the amino silica and propane sultone to the first solvent is 1:(2-5);
[0021] The first solvent includes one or more of acetone, acetonitrile, toluene, ether and methanol;
[0022] The second heating temperature is 80° C. and the time is 4 to 8 hours.
[0023] Preferably, the preparation method of the silica sol comprises: mixing tetraethyl orthosilicate, alcohol, water and inorganic acid, and sequentially performing hydrolysis and static aging to obtain the silica sol;
[0024] The volume ratio of tetraethyl orthosilicate, alcohol, water and inorganic acid is (1-5): (12-20): (0.5-1.5): 0.1;
[0025] The alcohol includes ethanol and / or propanol;
[0026] The mass percentage concentration of the inorganic acid is 20-40%, and the inorganic acid is nitric acid or hydrochloric acid;
[0027] The hydrolysis temperature is 20-25°C and the time is 1-6h;
[0028] The temperature of the static aging is room temperature, and the time is 1 to 3 days;
[0029] The mass ratio of the zwitterion-modified nano-silica spheres to the silica sol is 100:(1-10).
[0030] Preferably, the cross-linking agent is an acrylate cross-linking agent;
[0031] The mass ratio of the zwitterion-modified nano-silica spheres to the cross-linking agent is (10-100):1;
[0032] The photoinitiator includes one or more of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-methylphenylpropane-1-one, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and benzophenone;
[0033] The mass ratio of the zwitterion-modified nano-silica spheres to the photoinitiator is (50-200):1;
[0034] The titanium dioxide is nano titanium dioxide colloid, and the mass ratio of the nano titanium dioxide colloid to the silica sol is (1-3):1;
[0035] The second solvent includes ethanol and water in a mass ratio of 1:(1-5).
[0036] The present invention also provides an organic-inorganic hybrid wear-resistant anti-fog coating prepared by the preparation method described in the above technical solution.
[0037] The present invention also provides the use of the organic-inorganic hybrid wear-resistant anti-fog coating described in the above technical solution in the preparation of an organic-inorganic hybrid wear-resistant anti-fog coating.
[0038] The present invention also provides a method for preparing an organic-inorganic hybrid wear-resistant anti-fog coating, comprising the following steps:
[0039] A layer of organic-inorganic hybrid wear-resistant anti-fog coating is coated on the surface of the substrate by a dip-pull method, and then UV curing is performed to obtain the organic-inorganic hybrid wear-resistant anti-fog coating;
[0040] The organic-inorganic hybrid wear-resistant anti-fog coating is the organic-inorganic hybrid wear-resistant anti-fog coating described in the above technical solution.
[0041] Preferably, the pulling speed of the immersion pulling method is 10 to 200 mm / min;
[0042] The UV curing light wavelength is 365nm, and the light intensity is 180-210mW / cm 2, the illumination time is 1 to 3 hours, and the illumination temperature is room temperature.
[0043] The invention provides a method for preparing an organic-inorganic hybrid wear-resistant anti-fog coating, comprising the following steps: after hydrolyzing aminosilane, mixing the hydrolyzed aminosilane with a silicon dioxide dispersion liquid and performing a first heating to obtain amino silicon dioxide; mixing the amino silicon dioxide, propane sultone and a first solvent and performing a second heating to obtain zwitterion-modified nano silicon dioxide balls; and mixing the zwitterion-modified nano silicon dioxide balls, silica sol, titanium dioxide, a crosslinking agent, a photoinitiator and a second solvent to obtain the organic-inorganic hybrid wear-resistant anti-fog coating. The invention conducts zwitterionic modification on nano-silica spheres to enhance the hydrophilicity and antistatic properties of nano-silica microspheres. Titanium dioxide can photocatalytically degrade pollutants to improve the weather resistance of the coating and maintain the long-term hydrophilic effect on the surface of the coating. At the same time, the invention also utilizes the high bonding strength of inorganic silica sol with the substrate to form a strong bonding force with the surface of most materials to enhance the water resistance of the coating. The acrylic acid cross-linking agent is used to provide an organic cross-linking network to improve the film-forming performance and mechanical strength of the coating. The invention utilizes the high strength and strong hydrophilicity of the above-mentioned organic-inorganic components to provide a guarantee for the coating to achieve wear resistance, anti-fog and antistatic properties.
[0044] The present invention also provides a method for preparing an organic-inorganic hybrid wear-resistant anti-fog coating, comprising the following steps: using an immersion and pulling method to coat a layer of an organic-inorganic hybrid wear-resistant anti-fog coating on the surface of a substrate, and then performing UV curing to obtain the organic-inorganic hybrid wear-resistant anti-fog coating. The prepared organic-inorganic hybrid wear-resistant anti-fog coating contains a silica sol with high bonding strength and titanium dioxide that can absorb ultraviolet rays, thereby overcoming the shortcomings of poor stability and poor aging resistance of organic hydrophilic coatings, and having the advantages of wear resistance, antistatic, anti-fog and water resistance, and a simple production process that can meet practical application requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The static contact angle diagram (a) of the glass sheet modified with the organic-inorganic hybrid wear-resistant and anti-fog coating described in Example 1 and the static contact angle diagram (b) of the blank glass sheet;
[0046] Figure 2 This is the SEM image of the zwitterion-modified nano-silica spheres described in Example 1;
[0047] Figure 3 This is a physical picture of the glass sheet modified with the organic-inorganic hybrid wear-resistant and anti-fog coating described in Example 1 and a blank glass sheet being placed in a 60° C. water bath for 0 h, 3 h and 12 h;
[0048] Figure 4Schematic diagram of antistatic properties of a blank PET film and a PET film modified with an organic-inorganic hybrid wear-resistant and anti-fog coating as described in Example 1;
[0049] Figure 5 The contact angle of the modified organic-inorganic hybrid wear-resistant anti-fog coating described in Example 1 when immersed in water for different time periods;
[0050] Figure 6 This is the wear resistance test result of the glass modified with the organic-inorganic hybrid wear-resistant and anti-fog coating described in Example 1.
[0051] Figure 7 The anti-fog images and contact angles of the glass modified with the organic-inorganic hybrid wear-resistant anti-fog coating described in Examples 1, 2, 3, and 4 after friction. DETAILED DESCRIPTION
[0052] The present invention provides a method for preparing an organic-inorganic hybrid wear-resistant anti-fog coating, comprising the following steps:
[0053] After hydrolyzing the aminosilane, the hydrolyzed aminosilane is mixed with a silica dispersion and subjected to a first heating to obtain amino silica;
[0054] The amino-silica, propane sultone and the first solvent are mixed and heated for a second time to obtain zwitterion-modified nano-silica spheres;
[0055] The zwitterion-modified nano silica spheres, silica sol, titanium dioxide, a crosslinking agent, a photoinitiator and a second solvent are mixed to obtain the organic-inorganic hybrid wear-resistant anti-fog coating.
[0056] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0057] In the present invention, after hydrolyzing the aminosilane, the hydrolyzed aminosilane is mixed with a silicon dioxide dispersion and subjected to a first heating to obtain amino silicon dioxide.
[0058] In the present invention, the hydrolysis process preferably comprises: mixing the aminosilane, water and ethanol, and then performing hydrolysis under acidic conditions.
[0059] In the present invention, the aminosilane preferably includes one or more of N-aminoethyl-γ-aminopropyltrimethoxysilane, N,N-dimethyl-3-aminopropyltrimethoxysilane (KH556), N,N-diethyl-3-(trimethoxysilyl)propylamine, anilinomethyltriethoxysilane, γ-aminopropyltriethoxysilane and polyaminoalkyltrialkoxysilane; when the aminosilane is two or more of the above specific selections, the present invention does not have any special restrictions on the ratio of the above specific substances, and can be mixed in any ratio. In an embodiment of the present invention, the aminosilane can be N,N-dimethyl-3-aminopropyltrimethoxysilane.
[0060] In the present invention, the mass ratio of the aminosilane, water and ethanol is preferably (10-40): (2-15): (50-100), more preferably (20-40): (2-10): (50-80). In an embodiment of the present invention, the mass ratio of the aminosilane, water and ethanol can be 25:8:80, 20:8:70, 20:6:80 or 20:6:80.
[0061] In the present invention, the pH value of the acidic condition is preferably 2 to 6, more preferably 3 to 5. The acidic condition is preferably provided by acid solution, and the mass percentage concentration of the acid solution is preferably 30% to 40%, more preferably 35% to 38%. In the present invention, the acid solution is preferably one or more of acetic acid, nitric acid and hydrochloric acid, more preferably hydrochloric acid. When the acid solution is two or more of the above specific selections, the present invention does not have any special restrictions on the ratio of the above specific substances, and can be mixed in any ratio. In an embodiment of the present invention, the pH value of the acidic condition can be 4; the acid solution can be hydrochloric acid with a mass percentage concentration of 36%.
[0062] In the present invention, the hydrolysis temperature is preferably 15-25°C, more preferably 20-25°C; the hydrolysis time is preferably 1-5h, more preferably 1-3h. In the present invention, the hydrolysis is preferably carried out under stirring. The present invention does not have any special restrictions on the stirring process, and the process well known to those skilled in the art can be used. In an embodiment of the present invention, the hydrolysis temperature can be 21°C and the time can be 1h.
[0063] After the hydrolysis is completed, the present invention also preferably includes standing. The present invention has no special limitation on the standing process, and the standing process can be carried out using a process well known to those skilled in the art.
[0064] In the present invention, the silica dispersion preferably comprises silica nanoparticles and ethanol aqueous solution; the mass ratio of the silica nanoparticles to the ethanol aqueous solution is preferably 1:(10-40), more preferably 1:(15-35). In the present invention, the volume ratio of ethanol to water in the ethanol aqueous solution is preferably (1-5):1, more preferably (1-3):1. In an embodiment of the present invention, the mass ratio of the silica nanoparticles to the ethanol aqueous solution may be 1:27, 1:32 or 1:18; the volume ratio of ethanol to water in the ethanol aqueous solution may be 1:1 or 1.5:1.
[0065] In the present invention, the mass ratio of the hydrolyzed aminosilane to the silicon dioxide is preferably (1-4):1, more preferably (2-3):1; the first heating temperature is preferably 60°C; the time is preferably 4-8h, more preferably 4-6h. In an embodiment of the present invention, the mass ratio of the hydrolyzed aminosilane to the silicon dioxide may be 2:1, 2.5:1 or 4:3; the first heating temperature may be 60°C, and the time may be 5h.
[0066] After obtaining the amino silica, the present invention mixes the amino silica, propane sultone and the first solvent and performs a second heating to obtain zwitterion-modified nano silica spheres.
[0067] In the present invention, the mass ratio of the amino silica to propane sultone is preferably (1-3): 1, more preferably (1-2): 1. In an embodiment of the present invention, the mass ratio of the amino silica to propane sultone may be 1.5:1, 4:3 or 1:1.
[0068] In the present invention, the total mass ratio of the amino silica and propane sultone to the mass ratio of the first solvent is preferably 1: (2-5), more preferably 1: (4-5). In an embodiment of the present invention, the total mass ratio of the amino silica and propane sultone to the mass ratio of the first solvent can be 1: 5 or 7: 30.
[0069] In the present invention, the first solvent preferably includes one or more of acetone, acetonitrile, toluene, ether and methanol, more preferably methanol. When the first solvent is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the solvent can be methanol.
[0070] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.
[0071] In the present invention, the second heating temperature is preferably 80°C; the second heating time is preferably 4 to 8 hours, more preferably 5 to 8 hours. In an embodiment of the present invention, the second heating time may be 6 hours.
[0072] After the second heating is completed, the present invention also preferably includes washing and drying performed in sequence. The present invention does not have any special limitation on the washing and drying processes, and the washing and drying processes may be performed using processes well known to those skilled in the art.
[0073] After obtaining the zwitterion-modified nano silica spheres, the present invention mixes the zwitterion-modified nano silica spheres, silica sol, titanium dioxide, a crosslinking agent, a photoinitiator and a second solvent to obtain the organic-inorganic hybrid wear-resistant anti-fog coating.
[0074] In the present invention, the mass ratio of the zwitterion-modified nano-silica spheres to the silica sol is preferably 100:(1-10), more preferably 100:(1-5). In an embodiment of the present invention, the mass ratio of the zwitterion-modified nano-silica spheres to the silica sol can be 100:1 or 100:2 or 100:5.
[0075] In the present invention, the method for preparing the silica sol preferably comprises: mixing tetraethyl orthosilicate, alcohol, water and inorganic acid, and sequentially performing hydrolysis and static aging to obtain the silica sol.
[0076] In the present invention, the volume ratio of tetraethyl orthosilicate, alcohol, water and inorganic acid is preferably (1-5): (12-20): (0.5-1.5): 0.1, more preferably (2-5): (12-15): 1: 0.1, and most preferably (2-3): (12-13): 1: 0.1. In an embodiment of the present invention, the volume ratio of tetraethyl orthosilicate, alcohol, water and inorganic acid can be 12: 2: 0.3: 0.1, 12: 2: 1: 0.1 or 12: 4: 1: 0.1.
[0077] In the present invention, the alcohol preferably includes ethanol and / or propanol, more preferably ethanol. When the alcohol is ethanol and propanol, the present invention does not have any special restrictions on the amount of the ethanol and propanol, and can be carried out using a process well known to those skilled in the art. In an embodiment of the present invention, the alcohol can be ethanol.
[0078] In the present invention, the mass percentage concentration of the inorganic acid is preferably 20 to 40%, more preferably 30 to 40%. In the present invention, the type of the inorganic acid is preferably nitric acid or hydrochloric acid.
[0079] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.
[0080] In the present invention, the hydrolysis temperature is preferably 20-25°C; the time is preferably 1-6h, more preferably 1-3h. In the present invention, the hydrolysis is preferably carried out under stirring. The present invention does not have any special restrictions on the stirring process, and the process well known to those skilled in the art can be used. In an embodiment of the present invention, the hydrolysis temperature can be 25°C and the time can be 1h.
[0081] In the present invention, the temperature of the static aging is preferably room temperature, and the time of the static aging is preferably 1 to 3 days, more preferably 1 to 2 days. In an embodiment of the present invention, the time of the static aging can be 2 days.
[0082] In the present invention, the tetraethyl orthosilicate is hydrolyzed in an acidic environment to obtain silica sol.
[0083] In the present invention, the titanium dioxide is preferably nano titanium dioxide colloid; the particle size of the titanium dioxide in the nano titanium dioxide colloid is preferably 5nm. In the present invention, the titanium dioxide colloid is preferably anatase titanium dioxide with a solid content of 20±1% and a crystal form of 100%.
[0084] In the present invention, the mass ratio of the nano-titanium dioxide colloid to the silica sol is preferably (1-3):1, more preferably (2-3):1. In an embodiment of the present invention, the mass ratio of the nano-titanium dioxide colloid to the silica sol may be 2:1 or 2.5:1.
[0085] In the present invention, the crosslinking agent is preferably an acrylate crosslinking agent, more preferably one or more of ethylene glycol dimethacrylate, pentaerythritol triacrylate and pentaerythritol hexaacrylate. When the crosslinking agent is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the crosslinking agent can be pentaerythritol triacrylate or ethylene glycol dimethacrylate.
[0086] In the present invention, the mass ratio of the zwitterion-modified nano-silica spheres to the cross-linking agent is preferably (10-100): 1, more preferably (50-100): 1. In an embodiment of the present invention, the mass ratio of the zwitterion-modified nano-silica spheres to the cross-linking agent can be 50:1 or 100:1.
[0087] In the present invention, the photoinitiator preferably includes one or more of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (UV-2959), 1-hydroxycyclohexylphenyl ketone (UV-184), 2-hydroxy-methylphenylpropane-1-one, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and benzophenone (BP). When the photoinitiator is two or more of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and can be mixed in any ratio. In an embodiment of the present invention, the photoinitiator can be UV-184, UV-2959 or BP.
[0088] In the present invention, the mass ratio of the zwitterion-modified nano-silica spheres to the photoinitiator is preferably (50-200):1, more preferably (100-200):1. In an embodiment of the present invention, the mass ratio of the zwitterion-modified nano-silica spheres to the photoinitiator can be 100:1.
[0089] In the present invention, the second solvent preferably includes ethanol and water, and the mass ratio of the ethanol to water is preferably 1:(1-5), more preferably 1:(1-3). In an embodiment of the present invention, the mass ratio of the ethanol to water may be 1:1.
[0090] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.
[0091] The present invention also provides an organic-inorganic hybrid wear-resistant anti-fog coating prepared by the preparation method described in the above technical solution.
[0092] The present invention also provides the use of the organic-inorganic hybrid wear-resistant anti-fog coating described in the above technical solution in the preparation of an organic-inorganic hybrid wear-resistant anti-fog coating.
[0093] The present invention also provides a method for preparing an organic-inorganic hybrid wear-resistant anti-fog coating, comprising the following steps:
[0094] The organic-inorganic hybrid wear-resistant anti-fog coating is coated on the surface of the substrate by the dipping and pulling method, and then UV curing is performed to obtain the organic-inorganic hybrid wear-resistant anti-fog coating.
[0095] The present invention has no special limitation on the material of the substrate, and any material known to those skilled in the art can be used. In an embodiment of the present invention, the material of the substrate is glass or PET.
[0096] Before the coating, the present invention preferably pre-treats the substrate, and the pre-treatment preferably includes cleaning. The present invention does not have any special limitation on the cleaning process, and the cleaning process can be carried out using a process well known to those skilled in the art.
[0097] In the present invention, the pulling speed of the immersion pulling method is preferably 10 to 200 mm / min, more preferably 10 to 100 mm / min. In an embodiment of the present invention, the pulling speed of the immersion pulling method can be 60 mm / min.
[0098] In the present invention, the UV curing light wavelength is preferably 365nm, and the light intensity is preferably 180-210mW / cm 2 The illumination time is preferably 1 to 3 hours, and the illumination temperature is preferably room temperature. In an embodiment of the present invention, the illumination wavelength of the UV curing can be 365 nm, and the illumination intensity can be 210 mW / cm 2 The illumination time can be 1h and the illumination temperature can be room temperature.
[0099] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0100] Example 1
[0101] 12 mL of ethanol, 2 mL of ethyl orthosilicate, 1 mL of water and 0.1 mL of nitric acid with a mass concentration of 40% were mixed, stirred at 25° C. for 1 hour, and then allowed to stand for 2 days to obtain a silica sol;
[0102] KH556, water and ethanol were mixed evenly in a mass ratio of 25:8:80, and the pH value was adjusted to 4 with 36% hydrochloric acid, and the mixture was stirred for 1 hour and then allowed to stand to obtain hydrolyzed KH556;
[0103] 10 g of silica nanoparticles were ultrasonically dispersed in a mixture of 150 mL of water and 150 mL of ethanol, and then 20 g of the hydrolyzed KH556 was added, reacted at 60° C. for 5 h, and dried to obtain aminated silica;
[0104] Dissolve 3 g of the amino-modified silica and 3 g of propane sultone in 30 g of methanol, heat at 80° C. for 6 h, wash the product with ethanol and dry it to obtain zwitterion-modified nano-silica spheres;
[0105] According to the mass ratio of 10:0.2:0.1:0.1:0.1:100:100, the zwitterion-modified nano-silica, nano-titanium dioxide colloid (titanium dioxide having a particle size of 5 nm and a solid content of 20±1% and a crystal form of 100% anatase-type titanium dioxide), the silica sol, pentaerythritol triacrylate, UV-184, ethanol and water are uniformly mixed to obtain an organic-inorganic hybrid wear-resistant anti-fog coating;
[0106] The cleaned glass sheet was immersed in the organic-inorganic hybrid wear-resistant and anti-fog coating, and pulled out with a pulling machine at a speed of 60 mm / min. The wavelength was 365 nm and the light intensity was 210 mW / cm 2 The reaction was carried out at room temperature under UV light for 1 hour to obtain a glass sheet modified with an organic-inorganic hybrid wear-resistant and anti-fog coating;
[0107] Alternatively, the PET film is cleaned with ethanol ultrasonic cleaning, plasma cleaning for 3 to 5 minutes, and then immersed in the organic-inorganic hybrid wear-resistant anti-fog coating, and the coating is coated and UV-cured in the same manner to obtain a PET film modified with the organic-inorganic hybrid wear-resistant anti-fog coating.
[0108] Figure 1 The static contact angle diagram (a) of the glass sheet modified with the organic-inorganic hybrid wear-resistant anti-fog coating and the static contact angle diagram (b) of the blank glass sheet are shown in FIG. Figure 1 It can be seen that the surface contact angle of the organic-inorganic hybrid wear-resistant anti-fog coating in the glass sheet modified with the organic-inorganic hybrid wear-resistant anti-fog coating described in Example 1 is 2°, and the surface contact angle of the blank glass sheet is 17°;
[0109] Figure 2 is the SEM image of the zwitterion-modified nano-silica sphere, Figure 2 It can be seen that the modified silica spheres have regular morphology and an average particle size of about 200 nm;
[0110] The glass sheet modified with the organic-inorganic hybrid wear-resistant anti-fog coating described in Example 1 and a blank glass sheet were placed in a 60° C. water bath for 0 h, 3 h and 12 h. Figure 3 (in ① The glass sheet modified with the organic-inorganic hybrid wear-resistant and anti-fog coating as described in Example 1, ② is a blank glass sheet) as shown by Figure 3 It can be seen that the glass sheet modified with the organic-inorganic hybrid wear-resistant anti-fog coating described in Example 1 can quickly absorb water droplets and spread them into a transparent water film in the early stage of anti-fogging without affecting the base line of sight, while the blank glass surface will block the view due to the accumulation of water droplets. After several hours, the surface of the glass sheet modified with the coating still maintains the anti-fog effect and is transparent and fog-free, but the small water droplets on the surface of the blank glass accumulate and cause light refraction and block the line of sight;
[0111] A blank PET film and a PET film modified with an organic-inorganic hybrid wear-resistant anti-fog coating as described in Example 1 were respectively attached to fingers (eg Figure 4 As shown in the figure, a force of about 1N was applied, and the PTFE film was rubbed back and forth for 30 cycles at a constant speed. Then, a polystyrene foam ball was suspended above the PTFE film. A large number of foam balls were adsorbed on the surface of the blank PET film, while no foam balls were adsorbed on the surface of the modified PET film, indicating that the film has good antistatic properties.
[0112] The glass sheet modified with the organic-inorganic hybrid wear-resistant and anti-fog coating described in Example 1 was immersed in deionized water for 1, 3, 5, and 7 days respectively, and then taken out and the surface water vapor was blown away by nitrogen gas to measure the contact angle, wherein Figure 5 The contact angle of the modified organic-inorganic hybrid wear-resistant anti-fog coating described in Example 1 after being immersed in water for different time periods is obtained. Figure 5 It can be seen that after immersion for 7 days, the contact angle of the modified organic-inorganic hybrid wear-resistant anti-fog coating described in Example 1 increased from the initial 2° to 7°, and still maintained a super-hydrophilic state;
[0113] The glass modified with the organic-inorganic hybrid wear-resistant and anti-fog coating described in Example 1 was subjected to a wear resistance test. Figure 6 For the selection of non-woven fabric as the upper sample, the wear test results of 200g load reciprocating friction 1000 to 10000 times are as follows: Figure 6 It can be seen that after 10,000 times of friction and wear, the contact angle of the coating surface does not increase by more than 10 degrees, maintaining good wetting properties, and the coating has good wear resistance.
[0114] Example 2
[0115] 12 mL of ethanol, 4 mL of ethyl orthosilicate, 1 mL of water and 0.1 mL of nitric acid with a mass percentage concentration of 40% were mixed, stirred at 25° C. for 1 hour, and then allowed to stand for 2 days to obtain a silica sol;
[0116] KH556, water and ethanol were mixed evenly in a mass ratio of 20:8:70, and the pH value was adjusted to 4 with 36% hydrochloric acid, and the mixture was stirred at 21°C for 1 hour and then allowed to stand to obtain hydrolyzed KH556;
[0117] 10 g of silica nanoparticles were ultrasonically dispersed in a mixture of 200 mL of ethanol and 150 mL of water, and then 20 g of the hydrolyzed KH556 was added, reacted at 60° C. for 5 h, and dried to obtain amino-modified silica;
[0118] 4 g of the aminated silica and 3 g of propane sultone were dissolved in 30 g of methanol, heated at 80° C. for 6 h, and the product was washed with ethanol and dried to obtain zwitterion-modified nano-silica spheres;
[0119] According to the mass ratio of 10:0.5:0.2:0.1:0.1:100:100, the zwitterion-modified nano-silica, nano-titanium dioxide colloid (titanium dioxide having a particle size of 5 nm and a solid content of 20±1% and a crystal form of 100% anatase-type titanium dioxide), the silica sol, pentaerythritol hexaacrylate, UV-2959, ethanol and water are uniformly mixed to obtain an organic-inorganic hybrid wear-resistant anti-fog coating;
[0120] The cleaned glass sheet was immersed in the organic-inorganic hybrid wear-resistant anti-fog coating and pulled out with a pulling machine at a speed of 60 mm / min. The wavelength was 365 nm and the light intensity was 210 mW / cm 2 The reaction was carried out at room temperature under UV light for 1 hour to obtain a glass sheet modified with an organic-inorganic hybrid wear-resistant and anti-fog coating.
[0121] The lubricity, abrasion resistance and hydrophilicity of the organic-inorganic hybrid wear-resistant anti-fog coating prepared in this example are similar to those in Example 1.
[0122] Example 3
[0123] 12 mL of ethanol, 2 mL of ethyl orthosilicate, 1 mL of water and 0.1 mL of nitric acid with a mass percentage concentration of 40% were mixed, stirred at 25° C. for 1 hour, and then allowed to stand for 2 days to obtain a silica sol;
[0124] KH556, water and ethanol were mixed evenly in a mass ratio of 20:6:80, and the pH value was adjusted to 4 with 36% hydrochloric acid, and the mixture was stirred at 21°C for 1 hour and then allowed to stand to obtain hydrolyzed KH556;
[0125] 10 g of silica nanoparticles were ultrasonically dispersed in a mixture of 150 mL of water and 150 mL of ethanol, and then 25 g of the hydrolyzed KH556 was added, reacted at 60° C. for 5 h, and dried to obtain aminated silica;
[0126] 4 g of the aminated silica and 3 g of propane sultone were dissolved in 30 g of methanol, heated at 80° C. for 6 h, and the product was washed with ethanol and dried to obtain zwitterion-modified nano-silica spheres;
[0127] According to the mass ratio of 10:1:0.5:0.2:0.1:100:100, the zwitterion-modified nano-silica, nano-titanium dioxide colloid (titanium dioxide having a particle size of 5 nm and a solid content of 20±1% and a crystal form of 100% anatase-type titanium dioxide), the silica sol, pentaerythritol triacrylate, BP, ethanol and water are uniformly mixed to obtain an organic-inorganic hybrid wear-resistant anti-fog coating;
[0128] The cleaned glass sheet was immersed in the organic-inorganic hybrid wear-resistant and anti-fog coating, and pulled out with a pulling machine at a speed of 60 mm / min. The wavelength was 365 nm and the light intensity was 210 mW / cm 2 The reaction was carried out at room temperature under UV light for 1 hour to obtain a glass sheet modified with an organic-inorganic hybrid wear-resistant and anti-fog coating.
[0129] The lubricity, abrasion resistance and hydrophilicity of the organic-inorganic hybrid wear-resistant anti-fog coating prepared in this example are similar to those in Example 1.
[0130] Example 4
[0131] 12 mL of ethanol, 2 mL of ethyl orthosilicate, 0.3 mL of water and 0.1 mL of nitric acid with a mass percentage concentration of 40% were mixed, stirred at 25° C. for 1 hour, and then allowed to stand for 2 days to obtain a silica sol;
[0132] KH556, water and ethanol were mixed evenly in a mass ratio of 20:6:80, and the pH value was adjusted to 4 with 36% hydrochloric acid, and the mixture was stirred at 21°C for 1 hour and then allowed to stand to obtain hydrolyzed KH556;
[0133] 10 g of silica nanoparticles were ultrasonically dispersed in a mixture of 100 mL of water and 100 mL of ethanol, and then 20 g of the hydrolyzed KH556 was added, reacted at 60° C. for 5 h, and dried to obtain amino-modified silica;
[0134] 3 g of the aminated silica and 2 g of propane sultone were dissolved in 25 g of methanol, heated at 80° C. for 6 h, and the product was washed with ethanol and dried to obtain zwitterion-modified nano-silica spheres;
[0135] According to the mass ratio of 10:0.2:0.1:0.1:0.1:100:100, the zwitterion-modified nano-silica, nano-titanium dioxide colloid (titanium dioxide having a particle size of 5 nm and a solid content of 20±1% and a crystal form of 100% anatase-type titanium dioxide), the silica sol, pentaerythritol hexaacrylate, BP, ethanol and water are uniformly mixed to obtain an organic-inorganic hybrid wear-resistant anti-fog coating;
[0136] The cleaned glass sheet was immersed in the organic-inorganic hybrid wear-resistant and anti-fog coating, and pulled out with a pulling machine at a speed of 60 mm / min. The wavelength was 365 nm and the light intensity was 210 mW / cm 2 The reaction was carried out at room temperature under UV light for 1 hour to obtain a glass sheet modified with an organic-inorganic hybrid wear-resistant and anti-fog coating.
[0137] The lubricity, abrasion resistance and hydrophilicity of the organic-inorganic hybrid wear-resistant anti-fog coating prepared in this example are similar to those in Example 1.
[0138] The glass modified with the organic-inorganic hybrid wear-resistant anti-fog coating described in Examples 1, 2, 3, and 4 was rubbed back and forth 10,000 times with a load of 200 g, and then the contact angle of the coating surface was tested. The anti-fog effect diagram ( Figure 7 ),Depend on Figure 7 It can be seen that the glass modified with the organic-inorganic hybrid wear-resistant anti-fog coating described in Examples 1, 2, 3, and 4 still maintains hydrophilicity after friction and has an anti-fog effect. The coating has a certain wear resistance that meets the needs of practical applications.
[0139] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing an organic-inorganic hybrid wear-resistant anti-fog coating, characterized in that: The following steps are involved: After hydrolyzing the aminosilane, the hydrolyzed aminosilane is mixed with a silica dispersion and subjected to a first heating to obtain amino silica; The amino-silica, propane sultone and the first solvent are mixed and heated for a second time to obtain zwitterion-modified nano-silica spheres; The zwitterion-modified nano silica spheres, silica sol, titanium dioxide, a crosslinking agent, a photoinitiator and a second solvent are mixed to obtain the organic-inorganic hybrid wear-resistant anti-fog coating.
2. The preparation method according to claim 1, characterized in that The hydrolysis process comprises: mixing the aminosilane, water and ethanol, and then hydrolyzing under acidic conditions; The aminosilane includes one or more of N-aminoethyl-γ-aminopropyltrimethoxysilane, N,N-dimethyl-3-aminopropyltrimethoxysilane, N,N-diethyl-3-(trimethoxysilyl)propylamine, anilinomethyltriethoxysilane, γ-aminopropyltriethoxysilane and polyaminoalkyltrialkoxysilane; The mass ratio of aminosilane, water and ethanol is (10-40): (2-15): (50-100); The pH value of the acidic condition is 2 to 6; the acid solution providing the acidic condition is one or more of acetic acid, nitric acid and hydrochloric acid, and the mass percentage concentration of the acid solution is 30% to 40%; The hydrolysis temperature is 15-25° C. and the time is 1-5 hours.
3. The preparation method according to claim 1, characterized in that: The silicon dioxide dispersion comprises silicon dioxide nanoparticles and an ethanol aqueous solution; The mass ratio of the silicon dioxide nanoparticles to the ethanol aqueous solution is 1:(10-40); The volume ratio of ethanol to water in the ethanol aqueous solution is preferably (1-5):1; The mass ratio of the hydrolyzed aminosilane to the silicon dioxide nanoparticles is (1-4):1; The first heating temperature is 60° C. and the time is 4 to 8 hours.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the amino silicon dioxide to propane sultone is (1-3):1; The mass ratio of the total mass of the amino silica and propane sultone to the first solvent is 1:(2-5); The first solvent includes one or more of acetone, acetonitrile, toluene, ether and methanol; The second heating temperature is 80° C. and the time is 4 to 8 hours.
5. The preparation method according to claim 1, characterized in that: The preparation method of the silica sol comprises: mixing tetraethyl orthosilicate, alcohol, water and inorganic acid, and sequentially performing hydrolysis and static aging to obtain the silica sol; The volume ratio of tetraethyl orthosilicate, alcohol, water and inorganic acid is (1-5): (12-20): (0.5-1.5): 0.1; The alcohol includes ethanol and / or propanol; The mass percentage concentration of the inorganic acid is 20-40%, and the inorganic acid is nitric acid or hydrochloric acid; The hydrolysis temperature is 20-25°C and the time is 1-6h; The temperature of the static aging is room temperature, and the time is 1 to 3 days; The mass ratio of the zwitterion-modified nano-silica spheres to the silica sol is 100:(1-10).
6. The preparation method according to claim 1 or 5, characterized in that: The cross-linking agent is an acrylate cross-linking agent; The mass ratio of the zwitterion-modified nano-silica spheres to the cross-linking agent is (10-100):1; The photoinitiator includes one or more of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-methylphenylpropane-1-one, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and benzophenone; The mass ratio of the zwitterion-modified nano-silica spheres to the photoinitiator is (50-200):1; The titanium dioxide is nano titanium dioxide colloid, and the mass ratio of the nano titanium dioxide colloid to the silica sol is (1-3):1; The second solvent includes ethanol and water in a mass ratio of 1:(1-5).
7. The organic-inorganic hybrid wear-resistant and anti-fog coating prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the organic-inorganic hybrid wear-resistant anti-fog coating according to claim 7 in the preparation of an organic-inorganic hybrid wear-resistant anti-fog coating.
9. A method for preparing an organic-inorganic hybrid wear-resistant anti-fog coating, characterized in that: The following steps are involved: A layer of organic-inorganic hybrid wear-resistant anti-fog coating is coated on the surface of the substrate by a dip-pull method, and then UV curing is performed to obtain the organic-inorganic hybrid wear-resistant anti-fog coating; The organic-inorganic hybrid wear-resistant anti-fog coating is the organic-inorganic hybrid wear-resistant anti-fog coating according to claim 7.
10. The preparation method according to claim 9, characterized in that: The pulling speed of the immersion pulling method is 10 to 200 mm / min; The UV curing light wavelength is 365nm, and the light intensity is 180-210mW / cm 2 , the illumination time is 1 to 3 hours, and the illumination temperature is room temperature.
Citation Information
Patent Citations
Super-hydrophilic silica coating and preparation method thereof
CN109535780A
Super-hydrophilic self-cleaning coating material composition and preparation method thereof, and super-hydrophilic self-cleaning glass and preparation method thereof
CN110093050A
Preparation method of amphiphilic polymer anti-fog coating layer based on zwitterions
CN111484785A
Self-repairable anti-fog coating and preparation method thereof
CN111662604A
Transparent super-hydrophilic antifogging coating based on zwitter-ions and preparation method of transparent super-hydrophilic antifogging coating
CN118063829A